“Let Me Talk to My Manager”: Haggling in a Competitive Environment - Desai, Preyas S. and Purohit, Devavrat (Marketing Science, 2004)
Although negotiating over prices with sellers is common in many markets such as automobiles, furniture, services, consumer electronics, etc., it is not clear how a haggling price policy can help a firm gain a strategic advantage or whether it is even sustainable in a competitive market. In this paper, we explore the implications of haggling and fixed prices as pricing policies in a competitive market. We develop a model in which two competing retailers choose between offering either a fixed price or haggling over prices with customers. There are two consumer segments in our analysis. One segment, the hagglers, has a lower opportunity cost of time and a lower haggling cost than the other segment, the nonhagglers. When both retailers follow the same pricing policy, then a haggling policy is more profitable than a fixed-price policy only when the proportion of nonhagglers is sufficiently high. We find two kinds of prisoners' dilemma: under some conditions, a more profitable haggling policy can be broken by a fixed-price policy, and under other conditions, a fixed-price policy can be broken by a haggling policy. Surprisingly, we show that under some conditions, an asymmetric outcome with one retailer haggling and the other offering a fixed price is also an equilibrium.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTI4Ny9ta3NjLjEwNDAuMDA0NQ